2019
DOI: 10.1007/s11146-019-09720-0
|View full text |Cite
|
Sign up to set email alerts
|

Energy Efficiency Information and Valuation Practices in Rental Housing

Abstract: The consensus in the academic literature is that energy efficiency is associated with transaction value premiums, but it is not clear to what extent property appraisers take account of this. We decompose external appraisals of rental housing by international valuation firms in England and the Netherlands in two waves, keeping the samples of valued homes constant between these years. We find a notable change in the behavior of external property appraisers. In England, energy performance does not impact assessed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 33 publications
0
24
0
Order By: Relevance
“…As pointed out by An and Pivo (2020), energy efficiency is likely to improve the dwelling's market value, which in turn should lower the contemporaneous LTV. Chegut et al (2020) document that Dutch energy efficient dwellings were valued significantly higher in 2015 compared to the baseline year of 2010. This suggests that the reported contemporaneous LTV ratios in our panel data set, which covers the period January 2014 to May 2018, should reflect the market value of buildings' energy efficiency.…”
Section: Choice Of Variables and Summary Statisticsmentioning
confidence: 99%
“…As pointed out by An and Pivo (2020), energy efficiency is likely to improve the dwelling's market value, which in turn should lower the contemporaneous LTV. Chegut et al (2020) document that Dutch energy efficient dwellings were valued significantly higher in 2015 compared to the baseline year of 2010. This suggests that the reported contemporaneous LTV ratios in our panel data set, which covers the period January 2014 to May 2018, should reflect the market value of buildings' energy efficiency.…”
Section: Choice Of Variables and Summary Statisticsmentioning
confidence: 99%
“…Zhang et al (2020) found that green hotels can charge around 6.5 per cent more for rooms without a reduction in occupancy rates. Chegut et al (2020) analysed professional appraisals of rental housing, finding that energy efficiency has become important for valuations in more recent periods.…”
Section: Energy Effects On Real Estate Valuesmentioning
confidence: 99%
“…Globally, studies examining residential values, energy efficiency and ratings have increased over the past decade, with much of the research focused on the European policy environment, because of the introduction of the Energy Performance Certificate (EPC) across the United Kingdom (UK) and many European countries. For example, empirical studies examining price effects in the Netherlands [5,32,33], Scandinavia [34,35], Switzerland [36], Ireland [37,38], Germany [39,40], Italy [41], Spain [42] and the UK [43,44], as well as studies in Japan [45,46], Singapore [47], China [48,49,50,51], the United States [52,53,54,55] and Australia [56,57,58]. A detailed analysis can be found in the meta-analysis performed by Daly et al [59].…”
Section: Energy Efficiency Property Values and Valuationmentioning
confidence: 99%
“…The disconnect between empirical studies and valuation practice has been discussed at length by Warren-Myers [60], who identified the use of information and the barriers involved in translating empirical evidence of this nature into practice. Yet, Chegut et al [5] suggest that empirical studies may have influenced a change in valuers' practice in the UK and Netherlands markets. Their recent study examined assessed values between 2010 and 2015 for both regions; they found no significant relationship between energy efficiency and values in 2010, but, by 2015, they identified higher-rated energy efficiency labels did lead to higher valuations, indicating a green premium or a brown discount for low-rated properties in their UK analysis.…”
Section: Energy Efficiency Property Values and Valuationmentioning
confidence: 99%
See 1 more Smart Citation